Health promotion through youth empowerment to prevent and control smoking behavior: a conceptual paper. Issue 3 (9th February 2021) - Trisnowati, Heni; Ismail, Djauhar; Padmawati, Retna Siwi
Abstract : Purpose: This paper aimed to review globally the empowerment programs for the prevention and control of smoking behavior among youths, to examine the role of empowerment in health promotion, to explore the stages of health promotion through community empowerment strategies including planning, implementation and evaluation. Finally, this paper will develop a model of youth empowerment to prevent and control smoking behavior that reflects theory and experience drawn from the literature. Design/methodology/approach: This review synthesized articles on community empowerment and health promotion, youth empowerment programs for tobacco prevention and control globally from books and electronic databases from the Universitas Gadjah Mada (UGM) library in the publication period 2000–2020. Relevant literature was selected and critically reviewed which reflected the role empowerment in health promotion, stage of community empowerment strategy as described by Laverack and youth empowerment concept in tobacco control as described by Holden. Findings: Documents that specifically discuss empowerment programs for smoking prevention and control are still limited. The findings document that youth empowerment in tobacco control do not fully integrate the theory empowerment as described by Laverack and Holden. This paper provides information about the stages of youth empowerment, and a conceptual framework of youth empowerment for the prevention and control of smoking behavior. Youth empowerment is done through the direct involvement of youth in programs starting from program design, planning, implementation and evaluation. Indicators of the success of the empowerment process are reflected in the increase in the empowerment domain. Meanwhile, the output of empowerment can be seen from the individual- or group-level changes. Originality/value: This paper proposes a model of youth empowerment for the prevention and control of smoking behavior among youths based on theory and experience in the field.